2003
DOI: 10.1023/a:1026082904672
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A satellite DNA sequence of Parodon hilarii (named pPh2004) was isolated, cloned and sequenced. This satellite DNA is composed of 200bp, 60% AT rich. In situ hybridization (FISH) results revealed that the satellite DNA pPh2004 is located in the terminal regions of several chromosomes, forming highly evident blocks in some and punctual marks in others. The comparison between the FISH and C-banding results showed that the location of this satellite DNA coincides with that of most terminal heterochromatins. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…gomesi did not reveal any similarity among themselves or with any sequences deposited in GenBank to date (Table 3). This kind of dead-end result has been reported before when studying sequences present in the sex chromosomes of Leporinus elongatus (Nakayama et al 1994;Parisi-Maltempi et al 2007), Parodon hilarii Reinhardt, 1866 (Vicente et al 2003), Cydia pomonella L., 1758 (Fuková et al 2007) and Oryzias hubbsi Roberts, 1998 (Takehana et al 2012), for example. Of the seven distinct fragments analysed, only CgW9 evidenced similarity (∼73%) to a DNA transposon (Helitron-2 Dr) isolated from the genome of Danio rerio.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…gomesi did not reveal any similarity among themselves or with any sequences deposited in GenBank to date (Table 3). This kind of dead-end result has been reported before when studying sequences present in the sex chromosomes of Leporinus elongatus (Nakayama et al 1994;Parisi-Maltempi et al 2007), Parodon hilarii Reinhardt, 1866 (Vicente et al 2003), Cydia pomonella L., 1758 (Fuková et al 2007) and Oryzias hubbsi Roberts, 1998 (Takehana et al 2012), for example. Of the seven distinct fragments analysed, only CgW9 evidenced similarity (∼73%) to a DNA transposon (Helitron-2 Dr) isolated from the genome of Danio rerio.…”
Section: Discussionsupporting
confidence: 67%
“…Fishes, however, express all possible forms of sex determination systems somehow associated with the huge biodiversity levels observed among them (reviewed in Volff et al 2007). In the particular case of Neotropical fishes, female heterogamety was reported in Characidium Reinhardt, 1867 and Parodon genera Valenciennes, 1850 (e.g., Vicente et al 2003;Vicari et al 2008;Machado et al 2011), male heterogamety was found in, e.g., Hoplias malabaricus (Bloch, 1794) (Cioffi et al 2011(Cioffi et al , 2012, and other species have multiple sex chromosomes, such as Leporinus elongatus Valenciennes, 1850 (Parise-Maltempi et al 2007) or Harttia carvalhoi Miranda Ribeiro, 1939 (Cioffi et al 2012) among others. Despite the differences in sex chromosome determination, these chromosomes share some features: Y and W are mostly heterochromatic while X and Z usually have more euchromatic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published data were used from studies on the cytogenetic description of the species A. affinis, A. ibitiensis, Apareiodon sp., A. vladii, A. piracicabae, A. vittatus, P. moreirai, P. hilarii, P. nasus, and P. pongoensis (Jesus and Moreira-Filho 2000a, b;Vicente et al 2001;Centofante et al 2002;Vicente et al 2003;Bellafronte et al 2005;Rosa et al 2006;Vicari et al 2006;Bellafronte et al 2009), as well as the new chromosome data from the present study, for the construction of the representative idiograms of the karyotypes of these species based on C-banding chromosome markers and FISH with the 18S rDNA, 5S rDNA, and satellite DNA pPh2004 probes.…”
Section: Methodsmentioning
confidence: 78%
“…Heterochromatin was analyzed using the C-banding method (Sumner 1972), and nucleolar organizer regions (NORs) were detected using silver nitrate impregnation, following the method described by Howell and Black (1980). For the chromosome location of the rRNA genes and satellite DNA pPh2004, fluorescent in situ hybridization (FISH) was used with an 18S rDNA probe obtained from Prochilodus argenteus (Hatanaka and Galetti 2004), a 5S rDNA probe from Leporinus elongatus (Martins and Galetti 1999), and a satellite DNA pPh2004 probe from P. hilarii (Vicente et al 2003). The probes were labelled by nick translation reactions with biotin-16-dUTP (Biotin Nick Translation mix; Roche) and/or digoxigenin-11-dUTP (Dig-Nick Translation mix; Roche), following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation